HISTORY LEARNING BASED ON WORDWALL APPLICATIONS TO IMPROVE STUDENT LEARNING RESULTS CLASS X IPS IN MA AS'ADIYAH KETAPANG - Wayan Mertha, I; Mahfud, Mahfud (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The development of historical learning evaluation instruments is a development in the form of questions in Class X with the subject of History of Hindu-Buddhist influences in Indonesia, the sub-subject of learning Acculturation of Local Culture and Hindu-Buddhist which is validated by the validator before being tested on students. Testing questions to students was carried out using an evaluation tool in the form of a wordwall web application to improve student learning outcomes for class X social studies at MA As'adiyah Ketapang. The purpose of this research and development is to (1) measure the validity of the evaluation instrument for history learning based on the wordwall web application in class X IPS MA As'adiyah Ketapang students, (2) find out the increase in learning outcomes before and after using the wordwall web application-based learning evaluation instrument., (3) knowing the student's response to the attractiveness of the wordwall web application-based learning evaluation tool. This type of research is Research and Development (RnD) with the ADDIE model consisting of Analysis, Design, Development, Implementation and Evaluation. The results showed that the learning evaluation instrument was feasible to use based on the assessment of material experts, it was obtained a score of 76% in the fairly good category, design experts, which amounted to 98% in the very good category, and history teachers, namely 81.3% in the good category. The results of the response to attractiveness in the trial showed an average result of 90% and in the field trial there was an increase in learning outcomes with the results of the N-Gain trial with results of 44% in the high category, 50% in the medium category and 18.6% in the low category.